Role of Critical View of Safety in Laparoscopic Cholecystectomy - Shahzad, Talat; Khan, Nadir Saifullah; Khan, Ulas; Naz, Saman; Khan, Haris Ali; Saleem, Mohammad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Biliary injury is frequently seen as a complication after laparoscopic removal of gall bladder. In order to minimize the occurrence of this dreadful complication, “critical view of safety” involving dissection in the triangle of Calot’s and subsequent recognition of cystic structures before surgery has been proposed. Objective: To determine the role of critical view of safety in laparoscopic cholecystectomy. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Department of Surgery, Benazir Bhutto Shaheed Teaching Hospital Abbottabad from 1st January 2018 to 30th September 2019. Methods: Three hundred patients requiring laparoscopic cholecystectomy were enrolled. Before clipping, the cystic artery and duct were isolated by critical view of safety. Demographic data of patients in addition to occurrence of intra-operative or post-operative complications was recorded. Results: Majority of study participants were females, 264 (88%) females and 36 (12 %) males. Females were older than males (p>0.05). Operative findings included non inflamed gall bladders in 83% patients of which 90% were females and rest were males. Difficult cholecystectomy like acutely inflamed gall bladder was seen in 17% patients and out of those 13% were females. Most of the patients were discharged from hospital by the third post-operative day. Only one patient developed bile leak but that was due to cystic duct slipped ligature. Conclusions: The incidence of injury to biliary ducts during laparoscopic cholecystectomy can be minimized by application of “critical view of safety”.